The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1111/j.1741-2358.2000.00055.x
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines for Oral Health Care for Long‐stay Patients and Residents

Abstract: People in residential or continuing care have an equal right to good oral health as people residing in the community. Entry to residential or continuing care provides an opportunity to assess need, identify problems, improve oral and dental health thereby contributing to improved general health and quality of life. This document provides guidance to establish standards for oral health care which are appropriate to the needs, demands and choices of individuals whether they live in continuing or residential care… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
28
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(31 citation statements)
references
References 36 publications
1
28
0
2
Order By: Relevance
“…Gallagher and Fiske (30) suggested that the need for Special Care Dentistry (SCD) is the much-needed necessity of today's time. SCD can address the oral health care needs of people with profound and severe disabilities, who require personalized one on one care (37,39). Therefore, the Authors emphasized on the need for the commissioning of Dentists With Special Interests (DwSI), who may hold competencies between general and special dentists and may be able to, form a skilled workforce in order to address the unmet needs of people with learning disabilities (4,30).…”
Section: Discussionmentioning
confidence: 99%
“…Gallagher and Fiske (30) suggested that the need for Special Care Dentistry (SCD) is the much-needed necessity of today's time. SCD can address the oral health care needs of people with profound and severe disabilities, who require personalized one on one care (37,39). Therefore, the Authors emphasized on the need for the commissioning of Dentists With Special Interests (DwSI), who may hold competencies between general and special dentists and may be able to, form a skilled workforce in order to address the unmet needs of people with learning disabilities (4,30).…”
Section: Discussionmentioning
confidence: 99%
“…Standards for daily oral hygiene should be agreed and care givers trained in the provision of daily oral care (Fiske et al, 2000, BSDH et al, 2001). This will involve cleaning teeth and/or dentures effectively.…”
Section: Evidence-based Self Carementioning
confidence: 99%
“…However, there are several obstacles that stand between the institutionalized elderly and access to oral health care, namely, the high cost of the treatments, the lack of perception of their needs, the lack of education for oral health and the lack of preparation of health professionals (Dolan et al, 2005;Fiske et al, 2000).…”
mentioning
confidence: 99%
“…These programs should not only target the elderly but also the health professionals and caregivers responsible for these seniors, in order to make them aware of the importance of oral health in general health (Fiske et al, 2000).…”
mentioning
confidence: 99%